Influence of Oxygen Pressure on Growth of Si-Doped β-(AlxGa1 − x)2O3 Thin Films on c-Sapphire Substrates by Pulsed Laser Deposition. (24th April 2019) - Hassa, A.; Wenckstern, H. von; Vines, L.; Grundmann, M.
Abstract : Ga 2 O 3 is a deep-UV transparent semiconducting oxide being interesting for solar-blind photo detectors e.g. for flame or missile plume detection. The bandgap of about 4.9 eV can be increased by alloying with Al 2 O 3 . We have investigated β-(Al, Ga)2 O3 thin films grown by pulsed laser deposition (PLD) on (00.1) Al 2 O 3 with regard to the influence of the growth parameters such as growth temperature (T g ) and oxygen partial pressure ( p (O2 )) on the structural, optical and electrical properties of the samples. The thin films have (-201) orientation and the cation incorporation strongly depends on the deposition parameters. At a given T g, the incorporation of Al is favored for lower p (O2 ) due to higher dissociation energy of the Al-O bond compared to the Ga-O bond. At a given p (O2 ), the incorporation of Al is favored for higher T g due to desorption of gallium sub-oxides during growth.